Effects of Gelam Honey on sperm quality and testis of rat - Syazana .N.S; Hashida .N.H; Majid .A.M; Durriyah Sharifah .H.A; Kamaruddin .M.Y (Universiti Kebangsaan Malaysia, 2011)
The present study aimed to elucidate the possible protective effects of Gelam honey on sperm quality and testis histology against infertility related problems. Control and treated groups of 4 - 5 weeks old male Sprague-Dawley rats were force-fed daily with 1.0 mL/100 g body weight of normal saline (0.9%) and Gelam honey, respectively. After 60 days of treatments, reproductive organs of the anesthetized rats were removed to assess sperm parameters and histology of testis. Sperm count of treated group was significantly higher (18.85±3.72×105/mL) than control group (17.05±3.12×105/mL) (p<0.05). Based on sperm morphology, treated group showed significantly higher percentage of normal sperm (96.83±0.03%) as compared to control group (94.87±0.01%) (p<0.01). Head and tail abnormalities sperm were also significantly reduced in the treated rats (p<0.05). The number of spermatogenic cells in testis of treated group were abundant as compared to control group. Seminiferous tubules of treated group were densely packed with spermatogenic cells with small lumen filled up with sperm tail. This study suggested that Gelam honey has the potential to increase the fertility of male rats by increasing sperm count and number of sperm with normal morphology